1996
DOI: 10.1152/ajpcell.1996.271.4.c1325
|View full text |Cite
|
Sign up to set email alerts
|

A critical evaluation of resting intracellular free calcium regulation in dystrophic mdx muscle

Abstract: There are conflicting reports regarding whether resting free calcium levels ([Ca2+]i) are elevated in dystrophic mouse (mdx) myotubes and adult myofibers. We reinvestigated this question and found several lines of evidence supporting the hypothesis that increased calcium influx via leak channels leads to increases in resting [Ca2+]i. 1) Step calibration of fura 2/free acid in myofibers with use of microinjected Ca(2+)-ethylene glycol-bis(beta-aminoethyl ether)-N,N,N',N'-tetraacetic acid buffers revealed greate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
74
2
4

Year Published

2000
2000
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 116 publications
(85 citation statements)
references
References 45 publications
5
74
2
4
Order By: Relevance
“…Our finding of a decreased sensitivity of the Ca 2ϩ release channel (when stimulated by caffeine) is in contrast to previous reports of normal electrically elicited Ca 2ϩ transients in muscles from mdx mice (4,14,35). Data on caffeine-induced contraction in saponinskinned single fibers from mdx mice are conflicting, with either an increase or decrease in the amplitude of caffeine-induced contraction being reported (8,33).…”
Section: Discussioncontrasting
confidence: 99%
“…Our finding of a decreased sensitivity of the Ca 2ϩ release channel (when stimulated by caffeine) is in contrast to previous reports of normal electrically elicited Ca 2ϩ transients in muscles from mdx mice (4,14,35). Data on caffeine-induced contraction in saponinskinned single fibers from mdx mice are conflicting, with either an increase or decrease in the amplitude of caffeine-induced contraction being reported (8,33).…”
Section: Discussioncontrasting
confidence: 99%
“…Changes of Ca 2ϩ channel activities or appearance of novel forms of Ca 2ϩ leak channels, notably of stretch-activated Ca 2ϩ channels, have been reported (18,19). In addition, tetrodotoxin-sensitive spontaneous contractile activity of myotubes in culture exacerbates the stimulated Ca 2ϩ increases (12,13). We confirmed these observations since in more mature cultures (day 11) characterized by frequent spontaneous contractions, the peak increases caused by KCl was found to be significantly higher, both in the cytosol and in the sub-plasmalemmal space.…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that the defect in Ca 2ϩ homeostasis is exacerbated in mdx cells upon application of mechanical stress (12,13). A simple and physiological way to test this hypothesis is to prolong the time in culture.…”
Section: Subcellular Ca 2ϩ Handling Alterations In MDX Myotubes 4649mentioning
confidence: 99%
See 1 more Smart Citation
“…There is some controversy about this Ca 2ϩ elevation (1,4). Some groups (5,6) showed that basal cytosolic Ca 2ϩ concentration ([Ca 2ϩ ] c ) 1 was higher in dystrophic skeletal muscle cells relative to controls, whereas other laboratories (7,8) found that [Ca 2ϩ ] c was only increased under stress. To elucidate this contention, the redistribution of Ca 2ϩ into intracellular organelles should be examined.…”
Section: Exchanges During Kcl Depolarization These Newly Demonstratementioning
confidence: 99%